Enterprise-focused management changing the face of project management : the application of the Theory of Constraints to the enterprise management of companies Ted Hutchin. - Hutchin, Ted. (Thomas Telford, 2001)
This book represents a new voice in the drive for enterprise thinking within organisations. Although Enterprise Resource Planning and similar approaches are now commonplace in industry they continue to deliver disappointing results. This book will enable companies to finally turn their investment into bottom-line improvement. Based on the author's own research over a three year period in a number of different companies throughout Europe, Enterprise focused management discusses the key issues within organisations today. These companies, drawn from project based industries such as construction and high tech product development, understand the pressures to make profit both now and in the future. They have a wealth of data at their fingertips, yet remain unable to make sense of this mass of information. Using the rigour and logic of the Theory of Constraints to first analyse these difficulties, and then to propose a way forward, the book should be the first port of call for all working or preparing to work in such environments. The book contains essential case studies that highlight the many conflicts and problems faced by managers at all levels, from the project office to the main board. The approach outlined by the author offers a way to analyse the problems and develop workable solutions that address the revenue chain of the company, resulting in substantial improvement to the bottom-line. Using the laws of constraint management as a basis the book argues strongly for a robust and rigorous thinking process to successfully implement change. It does so in a manner that the readers should be able to replicate in their own organisation. Enterprise focused management will be essential reading for all involved in project management.